2022
DOI: 10.32457/riem25.1580
|View full text |Cite
|
Sign up to set email alerts
|

Sentido, redes y prácticas. Percepciones de la corrupción en gobiernos locales de la Macrozona Sur (Chile)

Abstract: Este artículo tiene como objetivo analizar la corrupción en municipios de la Macrozona Sur de Chile, identificando el sentido, las redes y prácticas que la configuran como un fenómeno social desde la percepción de una serie de actores locales. Para cumplir con esto se utilizó una metodología cualitativa. Se realizaron 159 entrevistas entre 2017 y 2020 a funcionarios municipales, autoridades locales, expertos en temas de corrupción y stakeholders (grupos de interés) que se vinculan al municipio. Los principales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Characterizing corruption using this analytical framework provides a detailed portrait of how corruption operates in a specific context. This analytical framework complements what other authors have already indicated about the complexity of the phenomenon (Berthin-Siles, 2008;Gorrochategui, 2000;Martínez-Cousinou & Andersson, 2009;Strach, Sullivan & Pérez-Chiqués, 2019;Zamudio-González, 2020), and, in turn, it allows us to transcend the dyadic meaning of corruption, replacing it with one that seeks to understand the consolidation of the phenomenon (Gofen et al, 2022;Lino et al, 2022;Moya-Díaz & Paillama-Raimán, 2022;Palacios-Garay et al, 2022;Pérez-Chiqués & Bustos, 2021;Zizumbo-Colunga & Meza, 2021). The MACC identifies four dimensions that are recurring to achieve the consolidation of corruption processes, with special emphasis on local governments :…”
Section: Analytical Framework For the Consolidation Of Corruption Pro...supporting
confidence: 60%
See 1 more Smart Citation
“…Characterizing corruption using this analytical framework provides a detailed portrait of how corruption operates in a specific context. This analytical framework complements what other authors have already indicated about the complexity of the phenomenon (Berthin-Siles, 2008;Gorrochategui, 2000;Martínez-Cousinou & Andersson, 2009;Strach, Sullivan & Pérez-Chiqués, 2019;Zamudio-González, 2020), and, in turn, it allows us to transcend the dyadic meaning of corruption, replacing it with one that seeks to understand the consolidation of the phenomenon (Gofen et al, 2022;Lino et al, 2022;Moya-Díaz & Paillama-Raimán, 2022;Palacios-Garay et al, 2022;Pérez-Chiqués & Bustos, 2021;Zizumbo-Colunga & Meza, 2021). The MACC identifies four dimensions that are recurring to achieve the consolidation of corruption processes, with special emphasis on local governments :…”
Section: Analytical Framework For the Consolidation Of Corruption Pro...supporting
confidence: 60%
“…It is a framework that originated in Mexico but expanded to other regions of the world. This framework has been used for the study of local governments (Bastidas-Vargas, 2023;Gofen, Meza, & Pérez-Chiqués, 2022;Lino, Azevedo, Aquino, & Steccolini, 2022;Mendoza-Figueroa, 2023;Moya-Díaz & Paillama-Raimán, 2022;Palacios-Garay, Rodríguez-Salazar, Fuerte-Montaño, & Pereyra-Zaldívar, 2022;Pérez-Chiqués & Bustos, 2021;Ramírez-Sánchez, 2021;Rentería, 2023;Santiago, 2023;Tirado-Teodocio, 2021;Zizumbo-Colunga & Meza, 2021) and it serves here to provide a different understanding of how anti-corruption policies are enacted and fail in the context of systemic corruption in local governments. Finally, the last section presents the main conclusions and practical takeaways for addressing the issue of corruption, considering a larger portion of its complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Caracterizar la corrupción utilizando este marco analítico permite tener un retrato detallado de la manera en que opera la corrupción en determinado contexto. Este marco analítico complementa lo que otros autores ya han señalado sobre la complejidad del fenómeno (Berthin-Siles, 2008;Gorrochategui, 2000;Martínez-Cousinou & Andersson, 2009;Strach, Sullivan & Pérez-Chiqués, 2019;Zamudio-González, 2020), y a su vez permite trascender el significado diádico de corrupción por uno que apela a conocer la consolidación del fenómeno (Gofen et al, 2022;Lino et al, 2022;Moya-Díaz & Paillama-Raimán, 2022;Palacios-Garay et al, 2022;Pérez-Chiqués & Bustos, 2021;Zizumbo-Colunga & Meza, 2021). El MACC identifica cuatro dimensiones que son recurrentes para lograr la consolidación de procesos de corrupción, con especial énfasis en los gobiernos locales :…”
Section: Marco Analítico De La Consolidación De Procesos De Corrupció...unclassified
“…Se trata de un marco originado en México, pero ampliado a otras regiones del mundo. Este marco ha sido utilizado para el estudio de gobiernos locales (Bastidas-Vargas, 2023;Gofen, Meza, & Pérez-Chiqués, 2022;Lino, Azevedo, Aquino, & Steccolini, 2022;Mendoza-Figueroa, 2023;Moya-Díaz & Paillama-Raimán, 2022;Palacios-Garay, Rodríguez-Salazar, Fuerte-Montaño, & Pereyra-Zaldívar, 2022;Pérez-Chiqués & Bustos, 2021;Ramírez-Sánchez, 2021;Rentería, 2023;Santiago, 2023;Tirado-Teodocio, 2021;Zizumbo-Colunga & Meza, 2021) y sirve aquí para entender de manera diferente la manera en que se accionan, y fracasan, las políticas anticorrupción en el contexto de la corrupción sistémica en los gobiernos locales. Finalmente, la última sección presenta las principales conclusiones y derivados de utilidad para atender el problema de la corrupción considerando una mayor porción de su complejidad.…”
Section: Introductionunclassified